Abnormal Frequency Mismatch Negativity in Early Psychosis Outpatient Subjects. (July 2020) - del Re, Elisabetta C.; Maekawa, Toshihiko; Mesholam-Gately, Raquelle I.; Wojcik, Joanne; Seidman, Larry J.; McCarley, Robert W.; Niznikiewicz, Margaret A.
Background . Abnormalities of mismatch negativity (MMN), an event-related potential, indexing preattentive mechanisms, are consistently reported in schizophrenia (SZ). MMN abnormalities elicited to different deviant types have been recently shown to distinguish among patients according to length of their illness as well as inpatient versus outpatient status, and to be modulated by premorbid IQ. The objective of this study was to evaluate the MMN elicited by both frequency and duration deviant stimuli in patients with early schizophrenia (EP) recruited from an outpatient clinic in Boston, Massachusetts. Methods . Twenty-two healthy controls (HC) and 22 age-, handedness-, and gender-matched EP were tested using a frequency and duration MMN paradigm. Clinical data were also collected. Results . Frequency MMN amplitude but not duration MMN was significantly reduced in EP relative to HC subjects ( P = .015). Conclusions . These results indicate that in this sample of early psychosis outpatient group, reductions in frequency MMN but not in duration MMN index clinical status. The relationship between age at first hospitalization and MMN frequency and duration amplitude and latency indicates that neurodevelopmental stage, auditory function, and clinical status are tightly linked.